2022
DOI: 10.3389/fonc.2022.947530
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: A novel therapeutic strategy and mechanism of action in glioma

Abstract: Glioma is the most common malignant tumor of the central nervous system and resistance is easily developed to chemotherapy drugs during the treatment process, resulting in high mortality and short survival in glioma patients. Novel therapeutic approaches are urgently needed to improve the therapeutic efficacy of chemotherapeutic drugs and to improve the prognosis of patients with glioma. Ferroptosis is a novel regulatory cell death mechanism that plays a key role in cancer, neurodegenerative diseases, and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 127 publications
(145 reference statements)
0
6
0
Order By: Relevance
“…Two Ferroptosis-related genes, GPX4 and SLC7A11, were found to be upregulated in glioblastoma, which might be associated with the development and progression of glioblastoma [140,141]. The NRF2 pathway can inhibit glioblastoma iron death by enhancing the cystine/glutamate reverse transporter System-Xc [142].…”
Section: Glioblastomamentioning
confidence: 99%
“…Two Ferroptosis-related genes, GPX4 and SLC7A11, were found to be upregulated in glioblastoma, which might be associated with the development and progression of glioblastoma [140,141]. The NRF2 pathway can inhibit glioblastoma iron death by enhancing the cystine/glutamate reverse transporter System-Xc [142].…”
Section: Glioblastomamentioning
confidence: 99%
“…One potential target is the ROS-activated GCN2-eIF2α-ATF4-xCT pathway which leads to mitochondrial dysfunction and cisplatin resistance . Gliomas are the most common malignant tumors in central nervous system, which can easily become resistant to chemotherapy drugs during treatment, leading to a poor prognosis for patients . Ferroptosis-related regulators (e.g., GPX4, SLC7A11 and FSP1) are closely associated with the management of brain diseases including gliomas, and the induction of ferroptosis could also ameliorate the drug resistance of glioma to chemotherapeutic drugs …”
Section: Ferroptosis Inducers and Their Application In Cancer Therapymentioning
confidence: 99%
“…Previous studies have reported that ferroptosis is reduced in tissues of glioma patients, and induction of ferroptosis is an effective strategy for treating glioma [16][17][18]. To further verify the role of ferroptosis in glioma, we retrieved the gene expression data of 19 ferroptosis suppressor genes with a confidence score of 3 or greater from the FerrDb website.…”
Section: The Relationship Between Cdca7 and Ferroptosis Suppressor Ge...mentioning
confidence: 99%
“…Both MYC and E2F1 are involved in regulating the occurrence and progression of ferroptosis [12][13][14], a newly discovered non-apoptotic cell death pattern characterized by an overwhelming iron-dependent accumulation of lethal lipid reactive oxygen species (ROS) [15]. While the dysregulation of ferroptosis is closely related to tumorigenesis and treatment, according to many previous studies, induction of ferroptosis was found to be effective in treating glioma [16][17][18]. Some studies also indicate that the over-expression of MYC and E2F1 has an inhibitory role in the occurrence of ferroptosis.…”
Section: Introductionmentioning
confidence: 99%